THE EFFECT OF MANDATORY IFRS ADOPTION ON EARNING MANAGEMENT AND POLITICAL CONNECTION AS MODERATION VARIABLES IN COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Wardhana Y.A.V.W. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This study aims to look at the effect of IFRS mandatory adoption role on earnings management and to see the effect of political connections in influencing IFRS adoption of earnings management. The data used in this study came from companies listed on Indonesia Stock Exchange in 2010-2015. This research uses a quantitative approach, using moderation regression and independent t-test to answer the research hypothesis. Discretionary accruals are used as earnings management proxies. To test the influence of political connections in strengthening IFRS adoption of earnings management, moderation regression was used as the model. The independent t-test results showed that there are insignificant differences in earning management after three years mandatory IFRS adoption in Indonesia. The first regression equation result shows that adoption of IFRS in companies listed on the IDX had a insignificant effect on earnings management. The results of the second regression equation show that political connections have a significant influence on management earnings. The third regression equation shows that political connection moderation variables significantly influenced IFRS adoption of earnings management.